Relationship between organizational reward satisfaction and work performance of human resource professional in group human capital sector, Maybank - Ahmad Ridzwan, Majid (2013)
Rewards always play a significant role in influencing company’s growth and employees’ retention. Employees in this new era are more interested in the way organization use its resources thus they seek better approach and effective organizational rewards practice as to be efficient as possible. Not to mention that organizational rewards are one of the key elements to reward high-performer and eventually resulting in better performance traction and high retention. Nevertheless employees’ perceptions toward rewards over its transparency, fairness and objectivity are always being the key over the satisfaction of the rewards itself. Hence this study investigates the relationship between organizational rewards and work performance. The target group is HR Professional in Maybank’s Malaysia. The HR professionals were given standardized questionnaire in respect of the rewards practice in Maybank and required to respond to those questions accordingly. The data was collected from 128 questionnaires returned, out of 312 questionnaires distributed. Regression analysis results showed weak relationship between two components of rewards tested against work performance and the other showed no relationship at all, thus having weak linear correlation with work performance